PEMBAGIAN ZONA PENANGANAN BANJIR SEBAGAI EVALUASI KAPASITAS DRAINASE KOTA LABUAN BAJO - Denik Denik; Dian Noorvy Khaerudin (Universitas Tribhuwana Tunggadewi Malang, 2016)
The rate of development of storage capacity drainage channels are often not as fast as the rain water runoff caused by land use change. Macro drainage system as the primary drainage system is a system of channels that accommodate and drain water from a rain water catchment area, this qualifies as rivers and canals which are generally used in planning the return period of between 5 to 10 years with a detailed topography measurements. Komodo in general, with the total area is 121 980 ha, nearly 40% of the topography between 0-100 m above sea level (m asl). Approximately 54% of the area is at an elevation of 100 to 500 m above sea level, while the remainder is at an elevation of 500 m above sea level up to 1000 m above sea level. City Topography Labuan Bajo including hilly. Ground elevation ranging from ± 0.00 m above sea level (m asl) up to ± 525 m above sea level. With conditions like this it is given form an effective drainage network for hilly areas in the district such as Komodo, Labuan Bajo is the return period discharge plan 10 m3 / sec. Parameter election is based on the amount of discharge runoff plan out to the primary drainage channel and on the basis of a comparison of the length of time the concentration of the root canal and the slope of the land.